Locomotion in Rodents and Small Carnivorans: Are they So Different? - Muñoz, Nahuel Antu (2021)
Rodents and carnivorans constitute two diverse clades with variable life habits. To analyze the common ecomorphological aspects of their limbs in relation to their different substrate uses, the shape of humerus and femur was explored using 3-D geometric morphometrics. The principal components and MANOVA analyses show that the shape of the humerus is similarly related to the substrate use and taxonomy, and the shape of the femur is heavily influenced by taxonomic differences. Nevertheless, beneath those differences in the latter, a relation with the proposed ecological categories is also found. The stronger ecomorphological correlation of the humerus with respect to the femur may indicate a differential selective pressure on each limb. This could be reflecting the greater involvement of the forelimb over the hind limb in several activities performed with the limbs such as digging and climbing. The combined analysis of two distantly related groups with diverse ecological characteristics allows a recognition of similar biological patterns hidden under taxonomic differences. Furthermore, the study of morphological similarities and differences underlying taxonomic variability may led to a more profound understanding of the evolution of the locomotor apparatus.